Intrinsic connections of macaque striate cortex: axonal projections of cells outside lamina 4C - Blasdel, GG (J Neurosci, 1985)
We have exploited a technique for making small injections of horseradish peroxidase into single cortical laminae in order to study axonal projections in macaque striate cortex. In the preceding paper (Fitzpatrick, D., J. S. Lund, and G. G. Blasdel (1985) J. Neurosci. 5: 3329–3349) we examined the projections of cells in lamina 4C--cells that receive most of their input from the lateral geniculate nucleus. The present paper deals with the projections of neurons that lie outside of lamina 4C. Among our findings are several projections that previously had not been described in the monkey. These include: a strong and precise (point-to-point) projection from lamina 4B to lamina 2/3A, a reciprocal projection from 2/3A back to 4B, a definite projection from lamina 4B to 5B, as well as a prominent input to lamina 6 from 5B. In many cases, we find it possible to trace the flow of visual information through several “circuits” in striate cortex that have, as their output, projections to extrastriate cortex or to the brainstem. Our results offer additional insights in this regard since we are able, in many cases, to compare the lateral spreads of particular projections. These vary and can be separated into at least three categories: those that terminate in a precise, point-to-point, fashion, those that spread widely, and those that terminate in a laterally periodic fashion. In several cases we find evidence for a correlation between specific patterns of projection and known physiological differences between the topographies of laminae that are connected. In cases where two laminae possess similar topographies (for example, where both contain orderly maps for orientation) their interconnections appear precise, with little diffuse spread. In cases where two laminae are characterized by strikingly different topographies (where, for example, one contains an orderly map for orientation and the other a precise map for retinotopic position, but no specificity for orientation), the connections appear more diffuse.